Studi Potensi Lokal Kampung Cilegong Desa Mekarwangi dengan Analisis Spirit of Place - Muhammar Khamdevi (Prodi Arsitektur Universitas Matana, 2018)
New city development, with a gated community approach by private property developers in the Tangerang Regency area, has potentially reducing the quality of local informal settlements to slums. Construction o concrete walls that separate formal and informal housing or between the rich and the poor produces an unequal gap and the absence of shared space. Mekarwangi Village is one of the affected villages. Avoiding negative impacts in the future, it needs good and sustainable planning, which is based on the study of local potential that can be integrated into formal housing with an analysis of spirit of place. The case study of this activity is located in Cilegong Kampong in Mekarwangi Village. What is the local potential of Kampung Cilegong? To get a depht analysis, this study uses qualitative methods. The purpose of this study is to find the local potential of Mekarwangi Village that can be developed in the future. The final result shows, that Cilegong Kampong in Mekarwangi Village has the potential as a Green Tourism Village.